Characterization of Urinary Tract Stones with Dual Energy Computed Tomography - Yadav, Baidyanath; Maharjan, Surendra (Radiography Open, 2017)
Introduction. Dual Energy Computed Tomography (DECT) scan can provides simple and reliable differentiation between uric acid and non-uric acid stones. The characterization of various stones was based on the dual energy ratio and x-ray attenuation or HU. Methodology. A prospective study was conducted among 101 adult patients in Tribhuvan University Teaching Hospital (TUTH), Nepal. Informed written consent was obtained from all the participants. The standard low doses CT KUB were performed in multi-slice CT scanner (Siemens Somatom Definition AS+ 128 slice) at 120 kVp and 250 mAs. When stones were detected, second dual energy scans using 80 kVp and 140 kVp were obtained focusing only on the region of stones for their characterization. After post processing and graphical analysis at Syngo Via work station, the components of the stones were identified. Statistical analysis was performed in SPSS v21.0 software. Results. Out of 101 patients, 49 (48.5%) had calcium oxalate stones, 17 (16.87%) had uric acid stones, 16 (15.8%) had hydroxyapatite, 15 (14.9%) had cystine and 4 (4%) had mixed type of stones. Dual energy ratios were ranged from 0.55-1.11 for uric acid stone, 1.12-1.24 for cystine and more than 1.24 for calcium oxalate and hydroxyapatite stones. The mean HU noted in our study were; for uric acid stones (461.12 ± 119 HU at 80 kV, 449 ± 98.5 HU at 140 kV), for cystine (870.79 ± 386 at 80 kV, 743 ± 341 at 140 kV), for calcium oxalate (1246 ± 448 at 80 kV, 915 ± 316 at 140 kV) for hydroxyapatite (1301 ± 387 at 80 kV, 896 ± 315 at 140 kV) and mixed stone had (779.25 ± 269 HU at 80 kV, 665.5 ± 252 HU at 140 kV).